Evaluating Parameter Transfer in FALQON Across Graph Families - Fumaco, Alisson dos Passos; Reballo, Marcos Vinicius; Barros, Fernando Augusto Caletti de; Thomaz, Gabriel Fernandes; Duzzioni, Eduardo I. (Anais do Simpósio Brasileiro de Computação e Comunicação Quânticas (SBCCQ), 2026)
We evaluate FALQON parameter transfer for Max-Cut, transferring sequences from small donors (n ∈ {8, 10, 12}) to 14-node recipients. Using 3-regular and Erdős–Rényi families, we show transfer success is dictated by the recipient graph, not the donor. Transfer excels for dense recipients—achieving high approximation ratios regardless of the donor—but remains challenging in sparse cross-family cases. Crucially, performance is highly resilient to donor size, with 8-node donors matching larger instances. Thus, cheap small graphs can provide robust parameters for larger targets, significantly reducing the measurement overhead of the feedback loop.